Pengaruh Limbah Genteng Beton terhadap Workability dan Kuat Tekan Beton - Sudarso Sudarso (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
This study investigates the effect of roof tile waste used as a partial replacement for fine aggregate on the fresh and hardened properties of concrete, with the aim of promoting more sustainable and environmentally friendly construction materials. The research employed an experimental laboratory method with quantitative analysis. Roof tile waste was incorporated into concrete mixtures at substitution levels of 0%, 5%, 10%, 15%, and 20% by weight of fine aggregate. The workability of fresh concrete was evaluated using slump tests in accordance with SNI 1972:2011, while compressive strength tests were conducted on cylindrical specimens after 28 days of curing based on SNI 1974:2011 standards. The results indicate that increasing the proportion of roof tile waste reduced concrete workability, as shown by a decrease in slump values from 10 cm in the control mix to 8 cm at the 20% replacement level. Compressive strength also exhibited a declining trend, decreasing from 14.63 MPa to 11.90 MPa at the highest substitution, representing an approximate reduction of 18.7%. Nevertheless, concrete containing 5% roof tile waste achieved a compressive strength of 14.32 MPa, which is comparable to normal concrete. These findings suggest that roof tile waste can be utilized as a partial fine aggregate replacement at limited levels. A 5% substitution was identified as the optimal proportion to maintain acceptable workability and strength while supporting sustainable concrete development.